Inhibitors in Nonsevere Hemophilia A: What Is Known and Searching for the Unknown - Abdi, Amal; Linari, Silvia; Pieri, Lisa; Voorberg, Jan; Fijnvandraat, Karin; Castaman, Giancarlo (Seminars in Thrombosis and Hemostasis, 2018)
Nonsevere hemophilia A (NSHA) is an inherited X-linked bleeding disorder, caused by mutations of the F8 gene, leading to decreases of clotting factor VIII (FVIII) levels to 1 to 40 IU/dL. Desmopressin is the first therapeutic option for NSHA, but 40 to 50% of patients fail to attain adequate postinfusion FVIII levels. Thus, in these cases, FVIII concentrates remain the mainstay of treatment. The development of neutralizing FVIII antibodies (inhibitors) is a major challenge with replacement therapy. In contrast to severe disease, NSHA patients have a lifelong risk of inhibitor development. Recent data indicate that inhibitors are associated with a deterioration of clinical outcome, illustrated by an increase in bleeding and mortality rate. F8 genotype is an important risk factor for inhibitor occurrence together with surgical interventions and a high dose of FVIII concentrate. Adequate prevention and treatment of inhibitors in NSHA patients is limited by a lack of understanding of the underlying immunological mechanisms. Elucidation of the immunology driving inhibitor development is required to identify high-risk patients, to understand the association between clinical risk factors and inhibitor occurrence, and to provide the opportunity to develop new preventive and therapeutic strategies.
Keywords: nonsevere hemophilia A; diagnosis; treatment; inhibitor development; immunological characteristics